A 2-item version of the Japanese Consultation and Relational Empathy measure: a pilot study using secondary analysis of a cross-sectional survey in primary care. (26th April 2022) - Takahashi, Noriyuki; Matsuhisa, Takaharu; Takahashi, Kunihiko; Aomatsu, Muneyoshi; Mercer, Stewart W; Ban, Nobutaro
Abstract: Background: The Consultation and Relational Empathy (CARE) measure is a patient-reported measure of physician empathy which is widely used internationally. The Japanese version of the CARE measure has very high internal reliability, suggesting that a shorter version may have adequate validity and reliability. Objective: To investigate a valid shorter version of the Japanese CARE measure. Methods: We conducted a pilot study using secondary analysis of previous data obtained from 9 general practitioners and 252 patients and used to develop the Japanese CARE measure. All 1, 023 possible combinations of the Japanese CARE items ( n = 1–10) were candidates for the short measure. The internal consistency (Cronbach's alpha) and the correlations between candidate short questionnaires and the original questionnaire were calculated. After selecting the most valid short questionnaire, inter-rater reliability was determined using generalizability theory, and construct validity (Spearman's rho) was determined using patient satisfaction. Results: Two items were selected for a pilot shorter version: item 6 "Showing care and compassion" and item 9 "Helping you to take control." These showed high internal consistency and correlations with the 10-item measure (Cronbach's alpha = 0.920, correlation = 0.979). Forty-five questionnaires per doctor allowed us to reliably differentiate between practitioners. The construct validity for the pilot short measure was high (Spearman's rho 0.706, P < 0.001). Conclusion: We generated a pilot 2-item version of the Japanese CARE measure. This pilot 2-item version provides a basis for future validation studies of short CARE measures in other languages.